Implant comparisons for grazing yearling steers - Laudert, S.; Corah, L.; Nelson, R.; Sauerwein, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three field trials were conducted with grazing yearling steers to compare Compudose® and Ralgro® implants. Compudose® and Ralgro® implants. Compudose®-implanted steers gained faster (P<.05) than controls. Ralgro® improved daily gain by 3.8%. No significant difference was found between implants.
Keywords: Beef; Grazing; Steers; Implants